Ethnic Tourism and Hill Tribes’ Prosperity of the Northern Thailand: The Moderation Effect of Government Interest and Politics - Siriyanun, Sirinya (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: The primary purpose of conducting this research is to evaluate the moderating effect of government interest and politics in the relationship between ethnic tourism and Hill-tribes prosperity. Design/ Approach: The study adopted the quantitative research approach in which the data was collected from 364 tour guides and residents engaged in the ethnic tourism of Northern Thailand. The study utilised the SEM technique in which CFA and path analysis has been utilised to study the research phenomenon based on the responses collected through a survey questionnaire. Findings: The study concluded that there is a significant effect of government interest and politics in the relationship between ethnic tourism and Hill-tribes prosperity. Limitations: The study has a limited scope as the researcher has merely focused on investigating the research phenomenon from the context of Hill-tribes Northern Thailand.